A Discourse Analysis of Interactional Sociolinguistic at A Market - Suparini, Nyoman Winda (STKIP AGAMA HINDU SINGARAJA, 2023)
This research aimed to observe the interactional sociolinguistic analysis at one of traditional market at Singaraja. In the interactional sociolinguistic observed, the researcher describes the types of the interactional sociolinguistic that dominantly occur in the seller and buyer’s conversation. The observation has done at Pasar Penarungan in 20 interlocution and described into several subjects; male and female. The result of this research shows that there are two types of interactional sociolinguistic found in the sellers and buyers’ interlocution. Those types are contextualization cues and indirectness. The result showed the most dominant type of Interactional Sociolinguistic type found at the market is the indirectness. It can be seen not only from the intention given by both seller and buyer at that situation, but they also used various gestures and expressions that indicates their meaning in those signal.